Enhancing English Speaking Skills Via Reading Among Second Language Learners - Aatham Lebbei Faheema Jahan; Mohamed Jabeer Fathima Sujani (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
This study aims to improve students' speaking skills through reading at KM/STR Muslim Madhya Maha Vidyalaya.Twenty Five students in the 12A Arts class participated in this study. Students had problems in speaking due to inadequate knowledge of the language which in turn made the students felt unconfident to speak. And the students were not familiar with various speaking activities facilitating them to speak. They read text to convey ideas and a lack of strategies when speaking. To help the students, an intervention plan was implemented during the period. The data were taken from the results of the pre-test, post-test and interview. The pre-test marks shows the level of the speaking before the implementation of teaching process. And the post-test marks shows the level of the students after the implementation plan. The findings reveal that the implementation of intervention plan helped the students improve their speaking skills of two indicators assessed: vocabulary and comprehension. The students reading and speaking capacity have been developed by 56.75% than the pre-test. Students manage to complete the tasks by conducting various activities during the teaching learning process. They succeed in improving their speaking skills and gaining their confidence. The students can evaluate their learning in pairs and group works.